Impact of a focus education in Zoom on COVID-19 vaccine hesitancy in Hong Kong parents of the preschoolers. Issue 5 (30th November 2022) - Wong, Wilfred Hing-sang; So, Hung-kwan; Rosa Duque, Jaime S.; Tso, Winnie Wan-yee; Chong, Patrick Chun-yin; Kwan, Mike Yat-wah; Lau, Yu-lung
ABSTRACT: Parental vaccine hesitancy is a major barrier to achieving high vaccination uptake among children, particularly in young children during the coronavirus disease 2019 (COVID-19) pandemic. Developing herd immunity is a critical concept for overcoming the current pandemic. The purpose of this study is to reduce parental vaccine hesitancy through a focused educational seminar in ZOOM and to empower parents who are concerned about vaccinating their children to communicate with medical experts during live seminars. Parents of preschoolers, teachers, and kindergarten principals from three local pre-school education and services associations attended live seminars. After attending seminars, parental willingness to vaccinate their children increased by 65%. The live Zoom seminar led by medical experts resulted in a decrease in vaccine hesitancy. Our findings support the creation of seminars that allow clients and medical specialists to communicate directly with one another. Offering an open and honest forum for people to express their concerns to medical experts could be a useful strategy for dealing with not only vaccination apprehension, but also other health-related emergencies.